Social Investment and Territorial Inequalities: Mapping Policies and Services in the Baltic States - Jurga Bucaite-Vilke (Peter Lang International Academic Publishing Group, 2022)
Drawing on recent research perspectives, the book discusses how social investment policies could be responsive to territorial inequalities in terms of better policy coordination, capacities, and institutional infrastructures' adaptability to territorial needs. By combining theoretical notions about territorial cohesion, territorial development, and social investment, the book provides an argument for the "territorialization of social investment policy" in the case of Lithuania. The contributions of various authors encourage a different way of looking at the territorial sensitivity of welfare policy strategies implemented in advantaged developing areas and those which are disadvantaged peripheral territories.
Keywords: 330; Baltic; Bučaitė; Inequalities; Investment; Jurga; Mapping; Mazeikiene; Natalija; Policies; Services; Social; States; Territorial; Vilkė; Winkelkötter